New strategies for lowering the costs of antiretroviral treatment and care for people with HIV/AIDS in the United Kingdom - Gazzard B; Moecklinghoff C; Hill A (ClinicoEconomics and Outcomes Research, 2012)
Brian Gazzard,1 Christiane Moecklinghoff,2 Andrew Hill31St Stephens Centre, Chelsea and Westminster Hospital, London, UK; 2Janssen, Neuss, Germany; 3Department of Pharmacology and Therapeutics, University of Liverpool, UKAbstract: In the UK, the annual cost of treatment and care for people with human immunodeficiency virus (HIV)/acquired immune deficiency virus (AIDS) rose by over 600% from £104 million in 1997 to £762 million in 2010; approximately two-thirds of the £762 million cost of treatment and care in 2010 was for the procurement of antiretrovirals and other related drugs. The number of people accessing care for HIV/AIDS rose from 22,000 in 2000 to 65,000 in 2009. Adoption of “test and treat” guidelines for treating all HIV-infected people with antiretrovirals would further increase the burden of costs. Given the current economic situation, there is now a new focus on strategies for treatment and care of people with HIV-1 infection which can maintain efficacy but at a lower cost. In this review, we propose three strategies which could potentially lower the costs of treatment and care, ie, stopping testing CD4 counts for patients with full HIV RNA suppression on antiretroviral treatment and recent CD4 counts above 350 cells/µL; more widespread use of generic antiretrovirals as replacements for patients currently taking patented versions; and use of darunavir-ritonavir monotherapy as a switch option for patients with full HIV RNA suppression on other antiretrovirals and no history of virological failure. However, it is important that high standards of clinical care are maintained despite cost-saving measures. Antiretrovirals with generic alternatives may have toxicity issues, eg, zidovudine and nevirapine. There could be ethical issues in starting patients on these drugs if they are currently tolerating other treatments. The use of darunavir-ritonavir monotherapy is not consistently recommended in international HIV treatment guidelines.Keywords: health economics, generics, darunavir-ritonavir monotherapy, nucleoside analogs, non-nucleoside reverse transcriptase inhibitors